2004
DOI: 10.1002/app.21278
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of low density polyethylene during extrusion. III. Volatile compounds in extruded films creating off‐flavor

Abstract: ABSTRACT:This study was aimed at finding a correlation between the experienced off-flavor in packaged foods and the presence of specific degradation products in PE packaging films. The possibility to trap degradation products by chemical reactions with scavengers, that is, zeolites and maleic anhydride grafted LLDPE, were investigated. This trapping would prevent the degradation products from migrating to the polymer film surface and further into food in contact with the film. This work concludes that off-flav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 10 publications
2
20
0
Order By: Relevance
“…As the drawback of such high‐temperature processing, however, some oxidized substances were found both in the smoke from extruded films3 and also in the films 4. The oxidized compounds lead to an “off‐flavor” that affects the taste of products in the food package 5, 6…”
Section: Introductionmentioning
confidence: 99%
“…As the drawback of such high‐temperature processing, however, some oxidized substances were found both in the smoke from extruded films3 and also in the films 4. The oxidized compounds lead to an “off‐flavor” that affects the taste of products in the food package 5, 6…”
Section: Introductionmentioning
confidence: 99%
“…With increasing pozzolan content, the odor intensity of the bio‐composites decreased. This result suggested that the thermal degradation gases from the matrix and bio‐flour were absorbed at the pore surface of the pozzolan, thereby preventing them from migrating into the final products 17. The odor intensity of PP‐RHF bio‐composites was much higher than that of PP‐WF bio‐composites at room temperature and 80 °C, indicating that the thermal stability of RHF was lower than that of WF and that RHF produced a larger amount of thermal degradation gases and products than WF during the extrusion process 18.…”
Section: Resultsmentioning
confidence: 99%
“…Also, due to the complexity of the bag manufacturing process, it is difficult to determine the exact composition of most bag films. However, it is known that degradation of the polymers and additives in SUBs occur most significantly during high‐energy processes, namely sterilization and film extrusion, which may produce degradation products such as bDtBPP, whose potential effects on cells maybe completely overlooked. This reality, combined with the low concentrations reported eliciting negative effects on cell growth makes it paramount that the appropriate solvent systems and analytical techniques for extractables and leachables (E&Ls) screening are being implemented that are sensitive enough to detect both low abundant leachates and capturing all leachables present …”
Section: Introductionmentioning
confidence: 99%